When markets collide : investment strategies for the age of global economic change - El-Erian, Mohamed A., 1958- (McGraw-Hill, 2008)
Written by the man who "Fortune" magazine refers to as a "Global Guru," "When Markets Collide" offers a cogent picture of the rapidly changing world financial system, and provides a detailed blueprint for capitalizing on the opportunities now available.